Creutzfeldt-Jakob disease with dizziness initially presenting to the otolaryngology department. Issue 3 (June 2023) - Hara, Satoshi; Inoshita, Ayako; Miyamoto, Nobukazu; Takata, Yusuke; Matsuoka, Rina; Anzai, Takashi; Nakamura, Masahiro; Ikeda, Katsuhisa; Matsumoto, Fumihiko
Abstract: Creutzfeldt-Jakob disease is a fatal transmissible prion disease of the central nervous system. Dizziness as an initial manifestation of Creutzfeldt-Jakob disease is rare. However, patients with Creutzfeldt-Jakob disease and dizziness may initially visit the otolaryngology department, but this is uncommon. We report the case of a 56-year-old woman with Creutzfeldt-Jakob disease who initially presented with dizziness as an emergency patient to the otolaryngology department. Primary position upbeat nystagmus was identified using a charge-coupled device camera with infrared illumination. Electronystagmography revealed impaired smooth pursuit and diminished optokinetic nystagmus. Based on these findings, we immediately suspected an intracranial cause of dizziness and reached a presumptive diagnosis of sporadic Creutzfeldt-Jakob disease, thus preventing severe transmission. This case emphasizes that Creutzfeldt-Jakob disease should be included as a differential diagnosis for patients with dizziness and abnormal eye movements, such as primary position upbeat nystagmus, which might be caused by intracranial disease.